2009
DOI: 10.1007/s12032-009-9187-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nucleotide excision repair ERCC2 and base excision repair APEX1 genes polymorphism and its association with recurrence after adjuvant BCG immunotherapy in bladder cancer patients of North India

Abstract: Our data suggested variant (AA) of ERCC2 312 AA genotype to be associated with high risk of tumor recurrence and reduced recurrence free survival in superficial bladder cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Before this study, an XPD polymorphism study was conducted on the same cancer in an Indian population (Gangawar et al, 2010) but it studied recurrence and progression of cancer with post-BCG immunotherapy. Moreover, the latter did not show any significant genotypic difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before this study, an XPD polymorphism study was conducted on the same cancer in an Indian population (Gangawar et al, 2010) but it studied recurrence and progression of cancer with post-BCG immunotherapy. Moreover, the latter did not show any significant genotypic difference.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Stern et al (2002) found a slight decrease in risk for the Gln/Gln genotype compared with the subjects with the Lys/Lys or Lys/Gln genotypes. No associations for the XPD polymorphism were found in a Turkish population (Narter et al, 2009), in an Indian population (Gangawar et al, 2010), in three Italian populations (Shen et al, 2003;Matullo et al, 2005;Covolo et al, 2008), in American-Caucasians (Gu et al, 2005), and in a German population (Sanyal et al, 2004). Different population groups have different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize the best available evidence, we selected 12 studies that met the inclusion criteria for this review article of which five studies were published prior to 2011. The associations of smoking with disease recurrence and progression, the two most important disease outcomes in NMIBC, are summarized in Table 1 [11][12][13][14][15][16][17][18][19][20][21][22]. Although there are minor variations in disease outcome definitions among studies, the definitions were sufficiently similar to allow for evidence synthesis.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 99%
“…The majority of studies (10 of 12) investigated the associations of smoking status with disease recurrence [11][12][13][14][15][16]17 19,20]. Attributable to variations in the study sample sizes, there were variations of the comparator groupings.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 99%
See 1 more Smart Citation